Pengawasan dan Penegakan Hukum dalam Pemberantasan Tindak Pidana Perpajakan di Indonesia - Aidhar Fakhry; Agus Widodo (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
The importance of the taxation system as an economic pillar becomes increasingly prominent in the face of the complexity of international relations and ongoing technological developments. This article discusses the challenges faced by Indonesia in optimizing tax revenue and controlling tax avoidance in the era of globalization. The phenomenon of tax avoidance, particularly involving renowned companies such as PT Bentoel and Google, is a central issue in the context of taxation law in Indonesia. Its impact is significant, with reports from the Tax Justice Network estimating the country's losses at US4.86 billion per year or approximately IDR 68.7 trillion. Tax avoidance not only has a negative impact on tax revenue but also has the potential to undermine the overall effectiveness of the taxation system. Indonesia is confronted with the expansion of tax avoidance practices, especially by companies listed on the Indonesia Stock Exchange, reinforcing the urgency to address this issue within the existing taxation legal framework. This research adopts a qualitative method with a focus on tax supervision and enforcement to explore efforts to combat tax crimes in Indonesia. Thus, this study is expected to provide an in-depth understanding of the root issues and formulate effective solutions to enhance the effectiveness of Indonesia's taxation system. The research findings are anticipated to serve as a foundation for the development of a more effective national fiscal policy, addressing loopholes in the taxation legal framework, and preventing detrimental tax avoidance practices.